Working with adolescents : constructing identity - Head, John (John O.) (Master classes in education series., 2002)
This work examines the way in which personality and identity of the pupil is shaped by his or her experiences in school. The text considers the way in which teachers in secondary schools are working, and to some extent living, with adolescent pupils for the majority of time in their weekday waking lives. The book examines: to what extent teachers provide both positive and negative role models for pupils to follow; the factors restricting the ability of teachers to teach effectively; and conversely, what factors work to their advantage.; The text provides an overview of the debates and research into areas of: teaching children about controversial subjects such as sex and drugs; gender differences; identities; peer groups; relations with adults; and beliefs and values.